Design, facile synthesis, and evaluation of novel spiro- and pyrazolo[1, 5-c]quinazolines as cholinesterase inhibitors: Molecular docking and MM/GBSA studies. (June 2018) - Gálvez, Jaime; Polo, Stivens; Insuasty, Braulio; Gutiérrez, Margarita; Cáceres, Daniela; Alzate-Morales, Jans H.; De-la-Torre, Pedro; Quiroga, Jairo
Graphical abstract: Highlights: We reported a facile and ecofriendly synthesis of novel spiro-pyrazolo[1, 5- c ]quinazolines. The compounds were evaluated as acetylcholinesterase and butyrylcholinesterase inhibitors. Molecular docking and binding free energy (ΔG) calculations indicated that the R-isomers could be involved in differential AChE activity. The compound 5f shown halogen bond interactions in the AChE's active site. Abstract: Given the wide spectrum of biological uses of pyrazolo[1, 5- c ]quinazoline and spiro-quinazoline derivatives as anticancer, anti-inflammatory analgesic agents, and their therapeutic applications in neurodegenerative disorders, it is compulsory to find easy, efficient, and simple methods to obtain and chemically diversify these families of compounds, thereby improving their biological applications. In this paper, we report the design and eco-friendly two-step synthesis of novel, fused spiro-pyrazolo[1, 5- c ]quinazoline derivatives as cholinesterase inhibitors. In addition, we studied their protein-ligand interactions via molecular docking and MM/GBSA calculations for a further rational design of more potent inhibitors. In first step, 2-(1 H -pyrazol-5-yl)anilines were obtained through microwave (MW) assisted solvent-free/catalyst-free conditions and the second step involved the synthesis of the spiro-pyrazolo[1, 5- c ]quinazolines by a cyclocondensation reaction between 2-(1 H -pyrazol-5-yl)anilines and cyclic ketones, or acetophenones, using stirring at room temperature. The compounds were obtained in high purity, good yields (50–97%), and at varying reaction times. The spiro-compounds were evaluated as acetylcholinesterase and butyrylcholinesterase inhibitors (AChEIs/BuChEIs) respectively, and the most potent compound exhibited a moderate AChE inhibitory activity (5f : IC50  = 84 μM). Molecular docking studies indicated that the binding mode of the compound 5f share common characteristics with the galantamine/donepezil-AChE complexes. Moreover, free binding energy (Δ G ) calculations showed a good agreement with the experimental biological activity values. Our theoretical results indicated that halogen bond interactions could be involved with differential potency of these compounds and provide a new starting point to design novel pyrazolo[1, 5- c ]quinazolines as new anti-Alzheimer agents.